Energy Management of a Hybrid Photovoltaic-Wind System with Battery Storage: A Case Report - Salah Ben Mabrouk; Salvatore Favuzza; Diego La Cascia; Fabio Massaro; Gaetano Zizzo (Journal of Sustainable Development of Energy, Water and Environment Systems, 2019)

(untitled)
This work presents a case report related to the management and the monitoring of a hybrid photovoltaic-wind system with battery energy storage, installed at the administrative offices building of the municipality of Valderice (Italy) within the framework of the Italy-Tunisia ENPI cooperation project Le Développement Durable Dans la Production Energétique Dans le Territoire (DE.DU.ENER.T.). The paper describes the hybrid system and briefly reports the monitoring data for a whole year, comparing the real production with the expected one and evaluating some performance indexes of the system. The performance indexes are very simple and have been defined only with the purpose of showing the advantages of distributed generation. Then, two different control logics for the battery energy storage systems are compared in order to define the most suitable management of the local energy resources, in presence of different Time-of-Use electricity tariffs. In particular, the two logics are compared by varying the difference between the electricity prices in peak hours and in off-peak hours and the rate between the electricity consumption of the building and the battery energy storage’s capacity.